An infectivity-enhancing site on the SARS-CoV-2 spike protein targeted by antibodies - Liu, Yafei; Soh, Wai Tuck; Kishikawa, Jun-ichi; Hirose, Mika; Nakayama, Emi E.; Li, Songling; Sasai, Miwa; Suzuki, Tatsuya; Tada, Asa; Arakawa, Akemi; Matsuoka, Sumiko; Akamatsu, Kanako; et al. (Cell, 2021)
Antibodies against the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein prevent SARS-CoV-2 infection. However, the effects of antibodies against other spike protein domains are largely unknown. Here, we screened a series of anti-spike monoclonal antibodies from coronavirus disease 2019 (COVID-19) patients and found that some of antibodies against the N-terminal domain (NTD) induced the open conformation of RBD and thus enhanced the binding capacity of the spike protein to ACE2 and infectivity of SARS-CoV-2. Mutational analysis revealed that all of the infectivity-enhancing antibodies recognized a specific site on the NTD. Structural analysis demonstrated that all infectivity-enhancing antibodies bound to NTD in a similar manner. The antibodies against this infectivity-enhancing site were detected at high levels in severe patients. Moreover, we identified antibodies against the infectivity-enhancing site in uninfected donors, albeit at a lower frequency. These findings demonstrate that not only neutralizing antibodies but also enhancing antibodies are produced during SARS-CoV-2 infection. [Display omitted] •SARS-CoV-2 infectivity is enhanced by specific antibodies independent of the Fc receptor•The open RBD state is induced upon antibody binding to a specific site on the NTD•Divalent bridging of spikes is required to induce the RBD-up state•Infectivity-enhancing antibodies are detected in severe COVID-19 patients A subset of antibodies detected in patients with severe COVID-19 target a specific region of the N-terminal domain of the spike protein and enhance binding of the virus to the ACE2 receptor.